Inorganic-organic hybrid pigments based on carminic acid and clay minerals. (June 2021) - Cavalcanti, Graycyellê R.S.; Rodrigues, Francisco; Zhuang, Guanzheng; Balme, Sebastien; Janot, Jean-Marc; Fonseca, Maria G.; Jaber, Maguy
Abstract: Hybrid pigments based on carminic acid (CA) stabilized by clay minerals have been prepared. Three different pathways were used: CA@saponite; CA@Al-pillared saponite; and hydrogels of saponite-CA or montmorillonite-CA covered by polyorganosilane (POS). Pigments were characterized by a set of different techniques including X-Ray diffraction (XRD), transmission electron microscopy (TEM), infrared spectroscopy (FTIR), solid state nuclear magnetic resonance (NMR) and time-resolved fluorescence (TRF) spectroscopies. The color parameters, i.e., L*a*b*, were measured. In addition, the photostability of the samples under visible light was evaluated. The results showed that CA@PilSap presented a greater stability compared to CA@Saponite. The pigments obtained from hydrogels presented the greatest light stability due to the coverage with POS that acts as a protective layer. Graphical abstract: Image 1 Highlights: New hybrid pigments based on carminic acid and clay minerals were prepared. The interactions at the molecular level were highlighted. The prepared pigments from hydrogels presented high stability under visible light. Coating with organosilanes may act as a protective layer for the pigments face to light exposure.